Periodisation of Primary and Secondary Technical and Vocational Education Development in the Republic of Bashkortostan - T. M. Aminov; R. M. Asadullin (Russian State Vocational Pedagogical University, 2020)
Introduction. Vocational education has always been and still is one of the main factors of successful sustainable development of society as a whole and of the individual in particular. Therefore, in the state policy of different countries of the world, including Russia, special attention is being given to the institutions, which train specialists for the leading sectors of the economy and production. For developing effective policy measures and predicting its effectiveness, it is essential to identify the potential of national vocational education system, to study its phase changes and evolution vectors, to analyse and summarise existing experience in the organisation of the system and to support its functioning at the national and regional levels.The aim of the present research is to identify and characterise the main periods of development of primary and secondary technical and vocational education in one of the major regions of Russia - the Republic of Bashkortostan.Methodology and research methods. The research methodology is based on the system and civilisational approaches. The retrospective analysis was conducted through historical, typological and comparative methods, as well as two conceptual models. In the first model, the pedagogical process is presented as a complete system determined by specific historical conditions. The second model, designed by one of the authors of this article, is based on the logic and structure of this process in its contemporary understanding. These concepts provide adequate analysis and extrapolation of historical and pedagogical experience into modern educational theory and practice.Results and scientific novelty. The authors identified socio-economic, pedagogical, organisational and managerial factors of periodisation of the system of primary and secondary technical and vocational education development of Bashkortostan. For the first time, at the local republican level, the main phases of the process have been identified and described, starting with the pre-institutional stage to the present day. It is demonstrated that the trajectory of gradual formation and improvement of the investigated directions and stages of vocational training in the territory of the Republic of Bashkortostan is regulated by the general laws on the development of social structures. Despite some specificity, the trends in regional education found are quite related to all-Russian processes.Practical significance. The research results can be useful and are already being used when developing and designing vocational development programmes, in particular, they enrich the content of such disciplines as "History of Pedagogy and Education", "History", various special courses and curriculum units, concerning the issues on the state and prospects of technical and vocational education. In addition, the research materials can be used for developing regional educational policy.